2022
DOI: 10.1167/iovs.63.9.14
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Cone Rod Dystrophy, Previously Assigned to a Missense Variant in RIMS1, Is Fully Explained by Co-Inheritance of a Dominant Allele of PROM1

Abstract: Purpose Autosomal dominant cone rod dystrophy 7 (CORD7) was initially linked to the gene RIMS1 and reported in a 4-generation British family in 1998. The purpose of this study was to investigate the legitimacy of this association, and to correctly characterize the genetic cause of this condition. Methods The allele frequency of RIMS1 c.2459G>A, p.Arg820His, was investigated in the Genomes Aggregation Dataset (gnomAD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…11 However, recent evidence questions the role of RIMS1 gene in the pathogenesis of cone–rod dystrophy type 7 and other retinal disorders. 30 In the case of our patient, no abnormal alterations in the rode–cone system were found on electrophysiological examination, making a diagnosis of cone–rod dystrophy type 7 unlikely.…”
Section: Discussionmentioning
confidence: 50%
“…11 However, recent evidence questions the role of RIMS1 gene in the pathogenesis of cone–rod dystrophy type 7 and other retinal disorders. 30 In the case of our patient, no abnormal alterations in the rode–cone system were found on electrophysiological examination, making a diagnosis of cone–rod dystrophy type 7 unlikely.…”
Section: Discussionmentioning
confidence: 50%
“…However, their scores in memory and executive function tests were variable, with some scores below average. The enhancement of some cognitive domains was attributed to genetic mutation rather than impaired visual function [ 19 , 20 ]. A kindred of four with the same PROM1 c.1117C > T p.Arg373Cys variant displayed superior memory recall.…”
Section: Discussionmentioning
confidence: 99%
“…Using an established paradigm to study cognitive function, one study reported a family with autosomal dominant cone-rod dystrophy and enhanced cognitive ability, who harboured a heterozygous missense variant (c.2459G > A, p.Arg820His) in RIMS1 , a gene known to be expressed in the ventricular zone, thalami, and hippocampus areas of the brain [ 19 ]. However, they subsequently reported co-inheritance of a heterozygous missense variant (c.1118C > T, p.Arg373Cys) in PROM1 [ 20 ], which is a gene known to be putative in adult hippocampal neurogenesis [ 21 ]. It is not known which gene/variant, or if both, may be associated with their augmented cognition.…”
Section: Introductionmentioning
confidence: 99%
“…RIMS1 has been previously associated with cone-rod dystrophy 7 (CORD7), and it is that association, reported in a four-generation non-consanguineous family [2], that has prompted the authors, and others, to take particular notice of variants in this gene in the context of retinal disease. We have very recently published our reassessment of the original family in whom RIMS1-associated disease was reported: the autosomal dominant cone-rod dystrophy is in fact attributable to a well-characterised pathogenic variant in the PROM1 gene (c.1118C>T, p.Arg373Cys) [3]. The phenotypes (ranging from macular, to cone-, or cone-rod, dystrophy) in the affected family members were in keeping with those reported for the PROM1 variant, and one member of that family was found to be affected despite not harbouring the RIMS1 variant.…”
mentioning
confidence: 99%